A theory‐based framework for understanding the establishment, persistence, and diffusion of community‐based conservation. Issue 1 (22nd October 2020) - Mahajan, Shauna L.; Jagadish, Arundhati; Glew, Louise; Ahmadia, Gabby; Becker, Hannah; Fidler, Robert Y.; Jeha, Lena; Mills, Morena; Cox, Courtney; DeMello, Nicole; Harborne, Alastair R.; Masuda, Yuta J.; et al.
Abstract: Over decades, biodiversity conservation researchers and practitioners have developed theories and conceptual frameworks to inform the planning, implementation, and evaluation of community‐based conservation (CBC). While a diversity of mechanisms for understanding and supporting CBC has helped tailor approaches to local needs and conditions, the absence of a unified lens to understand CBC has limited the capacity for integrating foundational theory into practice more systemically, and for learning across different projects, stakeholders, and institutions. We introduce a theory‐based framework called "the CBC framework" that draws upon three foundational theories from sociology, economics, and political science to understand the establishment, persistence, and diffusion of CBC. Experience applying aspects of the framework within different conservation organizations demonstrates how this integrative approach can provide a gateway for practitioners to engage with social science theory to understand the status and context of CBC interventions and efforts. For practitioners, scientists, evaluators, and strategists, the framework can guide the design of CBC interventions and monitoring and evaluation systems to facilitate theory‐based learning and enable evidence‐informed decision‐making. Approaches like the CBC framework that facilitate collaborative planning, evaluation, and research can help better integrate social science theory in conservation practice while increasing the capacity for conservation scientists, practitioners, and stakeholders to learn together and adaptively manage CBC to deliver positive results for both people and nature.